Mitral Valve Transcatheter Edge-to-Edge Repair Volumes and Trends - Kris Kumar; Timothy F. Simpson; Harsh Golwala; Adnan K. Chhatriwalla; Scott M. Chadderdon; Robert L. Smith; Howard K. Song; Ryan R. Reeves; Paul Sorajja; Firas E. Zahr (Journal of Interventional Cardiology)
Background. Despite an association between operator volumes and procedural success, there remains an incomplete understanding of the contemporary utilization and procedural volumes for mitral valve transcatheter edge-to-edge repair (MTEER). We aimed to identify annual operator procedural volumes, temporal trends, and geographic variability for MTEER among Medicare patients in the United States (US). Methods. We queried the National Medicare Provider Utilization and Payment Database for a CPT code (33418) specific for MitraClip device from 2015 through 2019. We analyzed annual operator procedural volumes and incidence and identified longitudinal and geographic trends in MTEER utilization. Results. From 2015 through 2019, a total of 27,034 MTEER procedures were performed among Medicare patients in the US. The nationwide incidence increased from 6.2 per 100,000 patients in 2015 to 23.8 per 100,000 patients in 2019, a 283% increase over the study period (Ptrend < 0.001). The incidence of MTEER by state varied by nearly 900% (range 5.5 to 54.9 per 100,000 person-years). In 2019, the mean annual MTEER operator annual volume was 9.1 MTEER procedures and had grown from 6.2 per year in 2015. Conclusions. In this nationwide study of Medicare beneficiaries in the United States, we identified a significant and sustained increase in the utilization of MTEER devices and operators and growth in annual procedural volumes from 2015 through 2019 with considerable variability in utilization by state. Further studies are needed to understand the clinical impact of variability in utilization and the optimal procedural volumes to ensure high efficacy outcomes and maintain critical access to MTEER therapies.